Effects of Fertilization and Competition Control on Tree Growth and C, N, and P Dynamics in a Loblolly Pine Plantation in North Central Florida. Issue 1 (17th January 2019) - Tumushime, Ignacie; Vogel, Jason G.; Minor, Marco N.; Jokela, Eric J.
Abstract : Core Ideas: The application of herbicide was critical for loblolly pine biomass to experience a growth increase with or without fertilizer early in the rotation but this effect decreased with time. The relatively muted response of tree productivity to fertilization was likely attributed to the site's high background soil fertility and overall quality. Future rotations may be affected by the retention or loss of soil nutrients as affected by silviculture. Silvicultural treatment (fertilization and competition control) effects on ecosystem C, N, and P accumulation were assessed in a 25‐yr‐old loblolly pine plantation for N and P (diammonium phosphate [ F DAP ] and triple superphosphate [FTSP ]) fertilizers, competition control (W), and combined treatments ( F DAP W or F TSP W ). End of rotation pine biomass C was estimated, and forest floor (Oi, Oe+Oa), and soils (0–10, 10–20, 20–50 and 50–100 cm) were analyzed for C, N and P content. The combined F and W treatment increased early growth, but only tree biomass C approached significant increases for F DAP W and F TSP W at rotation end. The combined F and W treatments significantly increased stem N content, and bark and foliage P content, but fertilization alone did not significantly increase nutrient content in pine tissues. Fertilization alone increased N and P content in the Oe+Oa horizon and some soil depths, while W alone decreased P in the Oe+Oa horizon. Extractable soil PO4 3− increased with F alone, but often decreased when F was combined with W. Results suggest that early increased growth effects from silviculture may not result in increased ecosystem C at the end of rotation, and that competition control may be required for fertilizer to affect N and P accumulation in pine. These results suggest that variation in background fertility and understory competition could modify silviculture's potential effects on fertilizer use efficiency and C sequestration in managed pine forests.